PROPOSED MARKETING STRATEGY FOR PRODUCT PHOTOGRAPHY CASE : ASA PROJECT (The Indonesian Journal of Business Administration, 2021)
With the current pandemic that is affecting every type of business in Indonesia and the World in general, the use of internet has been increasing 47% from the usual usage before the pandemic. This makes small business and medium business losing opportunity to make profits from their goods if they are not connected to the internet. So now many businesses are gradually making a move into the social media platforms to show their product and starting their business digitally. Asa Project is a Product Photography Studio that beginning its ventures because of the pandemic and is trying to help business that are in need of a cheaper alternative for product photography because of their needs in generating quality visual that can sell their goods. Because of that Asa Project must quickly make its mark on the market to get client awareness. To find the right marketing strategies this research uses qualitative method. By using an internal and external anlysis such as PESTEL, Marketing Mix. Another way is to benchmark competitors in the same or similar industry, by doing and in depth interview, to get information’s about how they practice their marketing and what their marketing strategies are. SWOT Matrix to identify the main problem for company and applied to the TOWS matrix. Based on exploratory, Asa project provide a easy to view social media that can help awareness. with invoices as list the services provided by TOWS Matrix and comprasion competitor in the similar company. For uses the systematic step contained the results in operational timeline and marketing timeline arranged within a period of six months budget. Keywords: Asa Project, Marketing strategies, Photography Studio, Social Media